El ánalisis de tareas para el desarrollo de competencias argumentativas en geometría - Calderon, Dora Inés (Revista Científica, 2006)
This article presents of a research in the ralation language development and development of mathematical knowledge, since an argumnetative perspective. The proposal Splits of the fundamental hypothesis that the developmentof a mathematical argument depends on a basic relation among the natural language as semiotic system that privileges the argument and the reasoning in genral, and mathematical reasoning in the elaboration of mathematical concepts such as the geometric concep. From that point of view, in the present study exists the interest to undersand, to describe, to analyze and to quality the processes in the classroom, both in the dimension of the teaching act and in the learning one, in the private fields of the language and the math. Thus, in this document is presented a priori and a posteriori, made from the model of the didactic engineering (Guy rousseau, 1998, 2004, and Régine Douady, 1984, among others). The design of taks was directed to the develoment (as the argumentative competences in geomety, in a group of students of 10 grado degree of secondary education. A specifc structuring for the analusis of a sequence of activites oriented is carried out to the reasoning processes development (as the argumentative one) and its relation with the processes of representation (like the semiotics process), in the formulation of a geometric relation:the Pythagoream raltion.